Jewish Families in Europe, 1939-Present History, Representation, and Memory - Michlic, Joanna Beata (HBI Series on Jewish Women, 2017)
This book offers an extensive introduction and 13 diverse essays on how World War II, the Holocaust, and their aftermath affected Jewish families and Jewish communities, with an especially close look at the roles played by women, youth, and children. Focusing on Eastern and Central Europe, themes explored include: how Jewish parents handled the Nazi threat; rescue and resistance within the Jewish family unit; the transformation of gender roles under duress; youth's wartime and early postwar experiences; postwar reconstruction of the Jewish family; rehabilitation of Jewish children and youth; and the role of Zionism in shaping the present and future of young survivors. Relying on newly available archival material and novel research in the areas of families, youth, rescue, resistance, gender, and memory, this volume will be an indispensable guide to current work on the familial and social history of the Holocaust.